Content and distribution of usnic acid enantiomers in three Icelandic lichen taxa - Aron Elvar Gylfason 1993- (2019)
Drug discovery has changed dramatically over the past years with the advent of new tools in chemical analytics and molecular biology. Successful discovery of new antibiotics, however, is rare. In addition to this, the overuse of antibiotics threatens their effectiveness due to increased resistance. Lichen species were used as traditional medicine prior to the discovery of the penicillin antibiotics and increased multidrug resistance has generated renewed interest in lichens. Usnic acid is one of the most common secondary lichen metabolites and is by far the most extensively studied. The (+)-enantiomer of usnic acid has more potent antimicrobial activity (especially against Gram-positive bacteria) whereas the ( ) enantiomer shows mild antifungal activity and strong phytotoxicity. In contrast to the vast number of papers describing the bioactivity of usnic acid, the characterization of usnic acid enantiomers is lagging behind. The aim of this project was to determine the content of total usnic acid and distribution of usnic acid enantiomers in three commonly occurring lichens in Iceland, Flavocetraria nivalis, Cladonia arbuscula and Alectoria ochroleuca. A UPLC-PDA-MS method was developed and validated for determination of total usnic acid content in lichens. The content of usnic acid ranged from 1.77% to 4.50%. The usnic acid peaks were fractionated using semi-preparative high-performance liquid chromatography (HPLC) and the chiral separation was performed using HPLC-UV. The ratio of (+)- and (-)-usnic acid varied substantially; Flavocetraria nivalis contained an average ratio of 1.76%:98.24%, Cladonia arbuscula contained an average ratio of 96.77%:3.23% and Alectoria ochroleuca contained only (-)-usnic acid. The complexity of usnic acid production has been revealed in our study of three commonly occurring Icelandic taxa. In light of pronounced antibiotic activities and intrinsic high contents of usnic acid, this work will have biological and ecological importance for future studies focusing on usnic ...